2017
DOI: 10.1002/adhm.201700254
|View full text |Cite
|
Sign up to set email alerts
|

Clickable Microgel Scaffolds as Platforms for 3D Cell Encapsulation

Abstract: While microporous scaffolds have been increasingly used for regenerative medicine and tissue repair applications, the most common techniques to fabricate these scaffolds use templating or top-down fabrication approaches. Cytocompatible bottom-up assembly methods afford the opportunity to assemble micro-porous systems in the presence of cells and create complex polymer-cell composite systems in situ. Here, microgel building blocks with clickable surface groups were synthesized for the bottom-up fabrication of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
146
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(146 citation statements)
references
References 36 publications
0
146
0
Order By: Relevance
“…[185][186][187] Building on this, the Anseth lab has reported a microporous microgel scaffold composed of multiarmed PEG-based polymers crosslinked via reactive octyneazide chemistry. [188] The microgels were synthesized via an inverse suspension polymerization, demonstrating control over particle size by changing the rate of shear applied. This particle assembly technique shows great promise, especially in advancing the field of injectable biomaterials.…”
Section: Solvent/additive-free Hydrogelsmentioning
confidence: 99%
“…[185][186][187] Building on this, the Anseth lab has reported a microporous microgel scaffold composed of multiarmed PEG-based polymers crosslinked via reactive octyneazide chemistry. [188] The microgels were synthesized via an inverse suspension polymerization, demonstrating control over particle size by changing the rate of shear applied. This particle assembly technique shows great promise, especially in advancing the field of injectable biomaterials.…”
Section: Solvent/additive-free Hydrogelsmentioning
confidence: 99%
“…We originally created microporous annealed particle (MAP) scaffolds as a way to combine microporosity and injectability, which showed a tremendous potential to heal wounds . We and others with similar technology have shown that in vitro, cells use these microporous scaffolds to expand and proliferate in three dimensions around the microparticles . These findings suggested that cells can be mixed with hydrogel immediately before delivery, and this can be used as a cellular delivery platform that can overcome some of the limitations of current hydrogel technologies.…”
mentioning
confidence: 99%
“…1E). Others and we have utilized MAP scaffolds for cell culture in vitro 24,[29][30][31][32][33][34][35] and support tissue ingrowth in vivo 24,[30][31][32] . HA-MAP scaffolds can be injected into the stroke core at 5-days post wounding without deforming the recipient hemisphere ( Fig.…”
Section: Characterization Of Map Hydrogel and Stroke Tissuementioning
confidence: 99%